Pembuatan Peta dan Sistem Informasi Geospasial Lahan Pertanian di Kecamatan Sentolo, Kabupaten Kulonprogo, Yogyakarta - Rochmad Muryamto; Waljiyanto Waljiyanto; Untung Rahardjo; Gondang Riyadi; Ruli Andaru; Iqbal Taftazani; Wahyu Marta; Annisa Farida (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2016)
Kulonprogo Regency as a part of Daerah Istimewa Yogyakarta Province has total agriculture land area about 10.700 hectare (Dinas Pertanian dan Kehutanan, 2014). Based on Daerah Istimewa Yogyakarta Local Regulation, No. 10 of 201, Article 9, Paragraph 2, Point (d) defined that sustainable food agriculture land area in Kulonprogo Regency only 5.029 hectare. Daerah Istimewa Yogyakarta Provincial Regulation No. 10 of 2011 about Sustainable Food Agriculture Land Protection mentioned that its necessary to maintain the activities of food security and sovereign, also prevent the farmland conversion to nonagricultural. The purpose of this society service is to make geospatial information system about agriculture land in a small part of agriculture area in Sukoreno Village, Sentolo Subdistrict, Kulonprogo Regency. In this society service, wide area mapping is about 10 hectare. The method that used for data record is aerial photo by Unmanned Aerial Vehicle (UAV). This method expected to be able to photograph whole agriculture area in Kulonprogo Regency quickly. The results of this society service are geospatial information system and agriculture land map that can used by Kulonprogo Regency Government to support sustainable food agriculture land protection activity.